2023
DOI: 10.16910/jemr.16.3.2
|View full text |Cite
|
Sign up to set email alerts
|

An Eye Tracking Based Framework for Safety Improvement of Offshore Operations

Muhammad Raza,
Raj Kiran,
Saima Ghazal
et al.

Abstract: Offshore drilling operations consist of complex and high-risk processes. Lack of situational awareness in drilling operations has become an important human factor issue that causes safety accidents. Prolonged work shifts and fatigue are some of the crucial issues that impact performance. Eye tracking technology can be used to distinguish the degree of awareness or alertness of participants that might be related to fatigue or onsite distractions. Oculomotor activity can be used to obtain visual cues that can qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Workers with high levels of SA can more acutely identify problems and propose solutions, which can be translated into experience after they have been validated in practice. Studies have demonstrated that those with high SA typically perform better at work [33,34].…”
Section: Situational Awareness In Constructionmentioning
confidence: 99%
“…Workers with high levels of SA can more acutely identify problems and propose solutions, which can be translated into experience after they have been validated in practice. Studies have demonstrated that those with high SA typically perform better at work [33,34].…”
Section: Situational Awareness In Constructionmentioning
confidence: 99%